2020
DOI: 10.1177/2042753020980120
|View full text |Cite
|
Sign up to set email alerts
|

Understanding kindergarten teachers’ perceptions of the use of touchscreen technologies: An exploratory study in mainland China

Abstract: Touchscreen technologies have become an important part of many young children’s lives. While kindergarten teachers’ perceptions of the use of touchscreen devices have been investigated across many countries, empirical research on the topic remains scant in mainland China. In an exploratory study, the lead researcher interviewed six teachers from an exemplary kindergarten in Nanjing and analyzed relevant documents to further explore the teachers’ beliefs around children’s use of touchscreen technologies. The Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Following the analysis of 11 studies, 8 showed various abilities that can be improved by integrating technology into the learning process. Yang & Gunn (2020) and Alkhawaldeh et al (2017) found that technology helps children learn numeracy. It also facilitates their ability to find and solve problems, which is a skill required in the future (Chen et al, 2018;Weng & Li, 2020).…”
Section: The Effect Of Using Digital Technology On Child Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the analysis of 11 studies, 8 showed various abilities that can be improved by integrating technology into the learning process. Yang & Gunn (2020) and Alkhawaldeh et al (2017) found that technology helps children learn numeracy. It also facilitates their ability to find and solve problems, which is a skill required in the future (Chen et al, 2018;Weng & Li, 2020).…”
Section: The Effect Of Using Digital Technology On Child Developmentmentioning
confidence: 99%
“…Another finding from this review was the supporting and inhibiting factors that affect the application of technology in early childhood education. The emergent supports were teachers' 1) awareness of the benefits in the classroom (Alkhawaldeh et al, 2017;Ihmeideh & Alkhawaldeh, 2017;Kara & Cagiltay, 2020;Kaynar et al, 2020;Weng & Li, 2020;Yang & Gunn, 2020), and 2) self-efficacy (Jeong & Kim, 2017).…”
Section: Supporting and Inhibiting Factors In The Application Of Tech...mentioning
confidence: 99%
See 1 more Smart Citation